Utilizing Spectral Indices to Estimate Total Dissolved Solids in Water Body Northwest Arabian Gulf - Al-Fartusi, Adel Jassim; Malik, Mutasim Ibrahim; Abduljabbar, Hameed Majeed (Marine Science Department Diponegoro University, 2023)
Remote sensing techniques have made it possible to monitor an important parameter of water quality, total dissolved solids (TDS), more appropriately and regularly. The research aims to assess Landsat 8 OLI images' ability to expose TDS on the sea surface in Iraqi marine waters. six band combinations were employed in the correlation analysis between band values and six dissolved solids samples collected during the fieldwork in three sampling stations to determine the amount of total dissolved solids (TDS): st1, st2, and st3 in December 2014 (26,38,36.9) g.L-1 and mid-January 2022 (27.4,37.9,37) g.L-1, respectively. Furthermore, two images of the Landsat-8 OLI satellite were captured concurrently with the gathering of samples for TDS detection at the measuring stations. After atmospheric correction and the add the remote sensing indicators, the reflectance of water was extracted from satellite images and utilized to express the spectral characteristics of various TDS concentrations, since the values were (22.64, 38, 32.46) g.L-1 in 2014, and (27.5, 36.68, 38) g.L-1 in 2022. Correlation coefficient (R2) values of 0.81, 0.96, and Pearson correlation (r) values of 0.90, 0.97 were found among field measurements and spectral data of TDS indicator 2 (SI-2) derived from green, blue, and red bands of Landsat -8 at 2014, 2022 respectively.